SISTEM INFORMASI GEOGRAFIS DAERAH RAWAN KRIMINALITAS DI KOTA PONTIANAK BERBASIS WEB - Septiandari, Sisilia Aveati (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2015)
Abstract - Criminality is human action that is in violation of or contrary to what is specified in the rule of law. Various forms of acts of criminality have been so rampant and troubling a lot of people in daily life. The most frequent cases occurred in the city of Pontianak was vehicle theft, the theft with the qualification and theft with violence. The number of cases increases which occurred in the town of Pontianak was almost entirely only note without visualize into digital form to be processed. This research aims to help the police in watching the level of criminality through spatial data or non-spatial data, so that it can control the area prone to criminality and crime-prone areas to provide information, for the public can be informed in anticipation of the crime-prone areas. The analysis is carried out using methods for Small Area Estimation (SAE) and Empirical Bayes (EB) to process data indicators and grouping the results the EB so can determine the priority of their respective district. System designed can help keep an eye on the level of criminality in the police force and can become information for the general public so that it can better anticipate crime-prone areas.